Titanium silical molecular sieve / mesophase aramid composite thin film dielectric material, preparation method and application thereof

CN122978488APending Publication Date: 2026-10-27STATE GRID ANHUI ELECTRIC POWER CO LTD ELECTRIC POWER SCI RES INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611189705.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-07-31
Filing Date
2026-08-06
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]为解决现有技术中高温储能薄膜在高温高电场下漏电流过大,击穿强度及充放电效率急剧下降的技术问题,本发明提供了一种钛硅分子筛/间位芳纶复合薄膜电介质材料及其制备方法

Benefits of technology

[0026](1)本发明首次将钛硅分子筛(TS-1)引入间位芳纶(PMIA)基体,通过TS-1表面钛羟基与PMIA酰胺基间的强氢键构建物理交联网络,无需化学改性,有效约束高温下分子链热运动,减少载流子产生,显著提升薄膜的高温绝缘性能与击穿强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978488A_ABST
    Figure CN122978488A_ABST
Patent Text Reader

Abstract

The application discloses a titanium-silicon molecular sieve / mesophase aramid composite thin film dielectric material and a preparation method and application thereof, and belongs to the technical field of polymer composite dielectric energy storage thin film preparation. The preparation method comprises the following steps: dissolving PMIA short fibers in a polar solvent containing LiCl, adding TS-1 dispersion, coating into a film through scraping, and preparing through water immersion, hot pressing and annealing. Strong hydrogen bonds are formed between titanium hydroxyl groups on the surface of TS-1 and amide groups of PMIA to construct a physical cross-linking network, so that the interface compatibility and high-temperature structural stability are improved. Meanwhile, high interface energy barriers are formed through interface energy band mismatching, charge injection and transportation are inhibited, high-temperature leakage current is significantly inhibited through the cooperation of the two, and the breakdown strength and energy storage density are improved. The application does not need chemical modification, and has the advantages of simple process, low cost and high compatibility with existing production lines, and has a wide application prospect in the field of high-temperature thin film capacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer composite dielectric energy storage film preparation technology, specifically relating to a titanium-silicon molecular sieve / meta-aramid composite film dielectric material, its preparation method, and its application. Background Technology

[0002] Polymer film capacitors are widely used in electric vehicles, aerospace electronics, and pulsed power systems due to their super-fast charging and discharging speeds, high power density, and excellent cycle stability. However, traditional polymer dielectric materials typically exhibit a sharp increase in conductivity loss and a significant decrease in breakdown strength at high temperatures. For example, commercially available biaxially oriented polypropylene (BOPP) film has a long-term operating temperature limit of only 105°C. Above this temperature, leakage current increases exponentially, leading to thermal breakdown failure and severely limiting its application in high-temperature environments.

[0003] Meta-aramid (PMIA) polymers, due to their molecular chain structure containing a large number of alternating amide groups and meta-benzene rings, possess excellent thermal stability (glass transition temperature > 270℃), intrinsic flame retardancy, good mechanical flexibility, and a high dielectric constant, making them ideal candidate dielectrics for next-generation high-temperature film capacitors. However, under high temperature and high electric field conditions, pure PMIA films exhibit exponential increases in leakage current with temperature and electric field strength due to intensified thermal motion of molecular chain segments, expansion of free volume, and the combined effects of electrode-injected charges and ionized carriers from internal impurities, leading to a significant decrease in breakdown strength.

[0004] To suppress charge carrier conduction at high temperatures, a common method is to introduce wide-bandgap inorganic nanofillers (such as Al2O3, SiO2, BNNS, etc.) into the polymer matrix to trap charge carriers by forming traps at the filler-matrix interface. Chinese patent CN118725367A discloses a technical solution for introducing titanium silicate molecular sieve (TS-1) into a polypropylene matrix, utilizing the pore structure of TS-1 to suppress electron avalanche breakdown. However, this solution requires complex chemical modification of TS-1 (silanol hydroxyl → amino → grafted polypropylene), and the temperature resistance of the polypropylene matrix itself is limited. Furthermore, the traditional inorganic filler and polymer matrix are mainly maintained by van der Waals forces or weak hydrogen bonds, resulting in weak interfacial interactions. This makes it difficult for the filler to achieve molecular-level dispersion and effectively utilize the constraint effect of physical cross-linking on molecular chain movement.

[0005] Therefore, there is an urgent need to develop a composite dielectric thin film material that can maintain excellent insulation performance at high temperatures without requiring complex chemical modification steps. Summary of the Invention

[0006] To address the technical problems of excessive leakage current, drastic decrease in breakdown strength and charge / discharge efficiency in existing high-temperature energy storage films under high temperature and high electric field conditions, this invention provides a titanium-silicon molecular sieve / meta-aramid composite thin film dielectric material and its preparation method. This invention utilizes the strong hydrogen bonding between the titanium hydroxyl groups and PMIA amide groups on the TS-1 surface to construct a physical cross-linked network. Simultaneously, it leverages the band mismatch at the interface to form a high interfacial energy barrier. This synergistically suppresses high-temperature leakage current from two dimensions: "constraining the thermal motion of molecular chains" and "blocking charge injection and transport," significantly improving the energy storage performance of the film under high temperature and high electric field conditions.

[0007] To achieve the above objectives, the technical solution of the present invention is as follows:

[0008] In a first aspect, the present invention provides a method for preparing a titanium-silicon molecular sieve / meta-aramid composite thin film dielectric material, comprising the following steps:

[0009] (1) Use anhydrous ethanol to clean the PMIA chopped fibers to remove surface impurities and then dry them;

[0010] (2) Add the dried PMIA chopped fibers to a polar solvent and add anhydrous LiCl as a co-solvent. Stir magnetically under heating conditions to completely dissolve the PMIA fibers and obtain a uniform and transparent PMIA dispersion.

[0011] (3) Add TS-1 powder to the above PMIA dispersion and continue to stir magnetically to make TS-1 fully dispersed in the PMIA matrix and fully contact the PMIA molecular chains to obtain a composite solution;

[0012] (4) The above composite solution is coated onto the substrate and heated and dried to allow the solvent to evaporate completely, thereby obtaining a composite film;

[0013] (5) Soak the composite film in deionized water for a long time to remove residual solvent and impurity ions;

[0014] (6) The composite film after soaking is subjected to hot pressing and annealing to obtain the final composite film dielectric material.

[0015] Preferably, the drying temperature in step (1) is 80-120℃ and the drying time is 2-4 h.

[0016] Preferably, the polar solvent in step (2) is N,N-dimethylacetamide (DMAc) or N-methylpyrrolidone (NMP), and the mass ratio of PMIA chopped fibers, polar solvent, and LiCl is (8-12):(85-90):(1-3). More preferably, the mass ratio of PMIA chopped fibers, polar solvent, and LiCl is 10:88:2.

[0017] Preferably, in step (2), the magnetic stirring speed is 400-800 rpm, the stirring temperature is 80-120℃, and the stirring time is 4-8 h.

[0018] Preferably, the amount of TS-1 powder added in step (3) is 0.1-5 wt% of the mass of PMIA solute, and more preferably 0.3 wt%.

[0019] Preferably, in step (3), the magnetic stirring speed is 400-800 rpm, the stirring temperature is 80-120℃, and the stirring time is 4-8 h.

[0020] Preferably, in step (4), the coating method is blade coating, the blade height is 180-220 μm, the coating speed is 10-30 mm / s, the drying temperature is 80-120°C, and the drying time is 10-12 h.

[0021] Preferably, in step (5), the temperature of the deionized water is 70-80℃, the soaking time is 4-8 days, and the water is changed 2-3 times a day.

[0022] Preferably, the hot pressing temperature in step (6) is 200±10℃, the hot pressing pressure is 0-5 MPa, and the hot pressing time is 30-60 s; the annealing temperature is 250±10℃, and the annealing time is 3-6 h.

[0023] Secondly, the present invention provides a titanium-silicon molecular sieve / meta-aramid composite thin film dielectric material prepared by the above preparation method.

[0024] Thirdly, the present invention provides the application of the above-mentioned composite thin-film dielectric material in the preparation of high-temperature thin-film capacitors.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) This invention introduces titanium silicon molecular sieve (TS-1) into meta-aramid (PMIA) matrix for the first time. A physical cross-linking network is constructed through strong hydrogen bonds between titanium hydroxyl groups on the surface of TS-1 and PMIA amide groups. No chemical modification is required. This effectively constrains the thermal motion of molecular chains at high temperatures, reduces the generation of charge carriers, and significantly improves the high-temperature insulation performance and breakdown strength of the film.

[0027] (2) The present invention utilizes the 2.53 eV band mismatch between TS-1 and PMIA to form a high interface energy barrier, which blocks electrode charge injection and deeply captures charge carriers. In synergy with hydrogen bond crosslinking, it suppresses high-temperature leakage current from the dual paths of "reducing the source" and "blocking the transmission", further enhancing the reliability of the film under high temperature and high field.

[0028] (3) The present invention optimizes the filler ratio to achieve uniform dispersion of TS-1 in the matrix, improves the compatibility of organic-inorganic interface and stability under long-term high temperature and high electric field; and the preparation process is simple, does not require surface grafting or coupling agent pretreatment, has low cost, is highly compatible with existing production lines, and is suitable for industrial production. Attached Figure Description

[0029] Figure 1 In the image, A is an optical photograph of the 0.3 wt% composite film of the present invention, B is a scanning electron microscope (SEM) photograph of the surface of the 0.3 wt% composite film, and C is a scanning electron microscope (SEM) photograph of the cross-section of the 0.3 wt% composite film.

[0030] Figure 2 In Figure A, the XRD curves of the 0.3 wt% composite film and the pure PMIA film of the present invention are shown; in Figure B, the FTIR curves of the 0.3 wt% composite film and the pure PMIA film are shown; in Figure C, the DSC curves of the 0.3 wt% composite film and the pure PMIA film are shown; and in Figure D, the DMA curves of the 0.3 wt% composite film and the pure PMIA film are shown.

[0031] Figure 3 This is a schematic diagram of the hydrogen bond physical cross-linking network between TS-1 and PMIA;

[0032] Figure 4 The dielectric frequency domain response characteristics of the 0.3 wt% composite film and the pure PMIA film of this invention at 150°C are shown.

[0033] Figure 5 The breakdown strength Weibull distribution of the 0.3 wt% composite film and the pure PMIA film of the present invention at 150°C is shown.

[0034] Figure 6 The leakage current density diagrams for the 0.3 wt% composite film and the pure PMIA film of this invention at 150°C are shown.

[0035] Figure 7 This is a band structure diagram of PMIA and TS-1 of the present invention (UV-vis+UPS test).

[0036] Figure 8 The diagram shows the energy storage performance of the 0.3 wt% composite film and the pure PMIA film of this invention at 150°C. Detailed Implementation

[0037] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of protection of this invention.

[0038] After reading the contents disclosed in this invention, those skilled in the art can make appropriate adjustments or substitutions to the process parameters of the methods and applications described in this invention without departing from the spirit and scope of this invention. Such obvious adjustments, substitutions or combinations should be included within the protection scope of this invention.

[0039] The sources of all raw materials used in this invention are not particularly limited; they can be purchased commercially or prepared using conventional methods well-known to those skilled in the art. The purity of all raw materials used in this invention is not particularly limited; however, analytical grade raw materials or raw materials with purity commonly used in the field of chemical synthesis are preferred.

[0040] Preparation of PMIA dispersion:

[0041] First, the PMIA chopped fibers were washed with anhydrous ethanol to remove surface impurities, and then dried in an 80°C oven for 2 hours. The dried PMIA chopped fibers and anhydrous LiCl were weighed and added together to a polar solvent. The polar solvent was N,N-dimethylacetamide (DMAc) or N-methylpyrrolidone (NMP), and the mass ratio of PMIA chopped fibers, polar solvent, and anhydrous LiCl was 10:88:2. The mixture was placed on a magnetic stirrer and stirred continuously at 400-800 rpm at 80-120°C for 4-8 hours until the PMIA fibers were completely dissolved, yielding an orange-yellow, homogeneous, and transparent PMIA dispersion.

[0042] In the following examples, unless otherwise specified, the PMIA dispersions were prepared according to the above method.

[0043] Example 1: A titanium-silicon molecular sieve / meta-aramid composite film

[0044] This embodiment provides a method for preparing a 0.3 wt% TS-1 / PMIA composite film, and the specific steps are as follows:

[0045] (1) Weigh TS-1 powder (the amount of TS-1 added is 0.3 wt% of the mass of PMIA solute) and add it to the above PMIA dispersion. Place the mixed solution on a magnetic stirrer and continue stirring at 600 rpm at 100°C for 6 h to fully disperse the TS-1 powder in the PMIA dispersion and obtain a uniform composite solution.

[0046] (2) The above composite solution was coated onto a clean glass plate using an adjustable doctor blade with a blade height of 200 μm and a coating speed of 20 mm / s. The plate was then dried in an oven at 80°C for 12 h to remove the polar solvent. After the solvent had completely evaporated, the glass plate and the film were removed together and placed in deionized water to allow the composite film to peel off on its own. The peeled composite film was then soaked in deionized water at 80°C for 4 days, with the water changed twice a day, to remove residual LiCl and solvent.

[0047] (3) Take out the soaked composite film, absorb the surface moisture with filter paper, place it in a flat vulcanizing machine, and hot press it at 200±10°C for 30 s with a pressure of 0~5 MPa. Then place the hot-pressed composite film in a vacuum drying oven at 250±10°C for annealing for 3 h, and take it out after naturally cooling to room temperature to obtain TS-1 / PMIA composite film, which is recorded as 0.3 wt% composite film.

[0048] Example 2: A titanium-silicon molecular sieve / meta-aramid composite film

[0049] This embodiment provides a method for preparing a 0.1 wt% TS-1 / PMIA composite film, and the specific steps are as follows:

[0050] (1) Weigh TS-1 powder (the amount of TS-1 added is 0.1 wt% of the mass of PMIA solute) and add it to the above PMIA dispersion. Place the mixed solution on a magnetic stirrer and continue stirring at 800 rpm at 80°C for 12 h to fully disperse the TS-1 powder in the PMIA dispersion and obtain a uniform composite solution.

[0051] (2) The above composite solution was coated onto a clean glass plate using an adjustable doctor blade with a blade height of 180 μm and a coating speed of 10 mm / s. The plate was then dried in an oven at 120°C for 10 h to remove the polar solvent. After the solvent had completely evaporated, the glass plate and the film were removed together and placed in deionized water to allow the composite film to peel off on its own. The peeled composite film was then soaked in deionized water at 70°C for 8 days, with the water changed twice a day, to remove residual LiCl and solvent.

[0052] (3) Take out the soaked composite film, absorb the surface moisture with filter paper, place it in a flat vulcanizing machine, and hot press at 200±10°C for 60 s with a pressure of 0~5 MPa. Then place the hot-pressed composite film in a vacuum drying oven at 250±10°C for annealing for 6 h, and take it out after naturally cooling to room temperature to obtain TS-1 / PMIA composite film, which is recorded as 0.1 wt% composite film.

[0053] Example 3: A titanium-silicon molecular sieve / meta-aramid composite film

[0054] This embodiment provides a method for preparing a 0.2 wt% TS-1 / PMIA composite film, and the specific steps are as follows:

[0055] (1) Weigh TS-1 powder (the amount of TS-1 added is 0.2 wt% of the mass of PMIA solute) and add it to the above PMIA dispersion. Place the mixed solution on a magnetic stirrer and continue stirring at 600 rpm at 120°C for 8 h to fully disperse the TS-1 powder in the PMIA dispersion and obtain a uniform composite solution.

[0056] (2) The above composite solution was coated onto a clean glass plate using an adjustable doctor blade with a blade height of 220 μm and a scraping speed of 30 mm / s to form a film. The film was then dried in an oven at 100°C for 11 h to remove the polar solvent. After the solvent had completely evaporated, the glass plate and the film were removed together and placed in deionized water to allow the composite film to peel off on its own. The peeled composite film was then soaked in deionized water at 70°C for 8 days, with the water changed twice a day, to remove residual LiCl and solvent.

[0057] (3) Take out the soaked composite film, absorb the surface moisture with filter paper, place it in a flat vulcanizing machine, and hot press at 200±10°C for 60 s with a pressure of 0~5 MPa. Then place the hot-pressed composite film in a vacuum drying oven at 250±10°C for annealing for 6 h, and take it out after naturally cooling to room temperature to obtain TS-1 / PMIA composite film, which is recorded as 0.2 wt% composite film.

[0058] Example 4: A titanium-silicon molecular sieve / meta-aramid composite film

[0059] This embodiment provides a method for preparing a 0.4 wt% TS-1 / PMIA composite film, and the specific steps are as follows:

[0060] (1) Weigh TS-1 powder (the amount of TS-1 added is 0.4 wt% of the mass of PMIA solute) and add it to the above PMIA dispersion. Place the mixed solution on a magnetic stirrer and continue stirring at 500 rpm at 110°C for 6 h to fully disperse the TS-1 powder in the PMIA dispersion and obtain a uniform composite solution.

[0061] (2) The above composite solution was coated onto a clean glass plate using an adjustable doctor blade with a height of 200 μm and a scraping speed of 20 mm / s. The plate was then dried in an oven at 100°C for 11 h to remove the polar solvent. After the solvent had completely evaporated, the glass plate and the film were removed together and placed in deionized water to allow the composite film to peel off on its own. The peeled composite film was then soaked in deionized water at 70°C for 8 days, with the water changed twice a day, to remove residual LiCl and solvent.

[0062] (3) Take out the soaked composite film, absorb the surface moisture with filter paper, place it in a flat vulcanizing machine, and hot press it at 200±10°C for 60 s with a pressure of 0~5 MPa. Then, place the hot-pressed composite film in a vacuum drying oven at 250±10°C for annealing for 6 h, and take it out after naturally cooling to room temperature to obtain TS-1 / PMIA composite film, which is recorded as 0.4 wt% composite film.

[0063] Comparative Example 1: Preparation of Pure PMIA Thin Film

[0064] This comparative example provides a method for preparing a pure meta-aramid (PMIA) film, and the specific steps are as follows:

[0065] (1) Following the above method for preparing PMIA dispersion, weigh 1 g of dried PMIA chopped fibers and 0.2 g of anhydrous LiCl, and add them together to 8.8 g of N,N-dimethylacetamide (DMAc) solvent. Place the mixture on a magnetic stirrer and stir continuously at 600 rpm at 100°C for 8 h until the PMIA fibers are completely dissolved to obtain PMIA dispersion.

[0066] (2) The above PMIA dispersion was coated onto a clean glass plate using an adjustable doctor blade with a height of 200 μm and a coating speed of 20 mm / s. The plate was then dried in an oven at 80°C for 12 h to remove the polar solvent. After the solvent had completely evaporated, the glass plate and the film were removed together and placed in deionized water to allow the film to peel off on its own. The peeled film was then soaked in deionized water at 80°C for 4 days, with the water changed twice a day, to remove residual LiCl and solvent.

[0067] (3) Take out the soaked film, dry the surface moisture with filter paper, place it in a flat vulcanizing machine, and hot press it at 200°C for 30 s with a pressure of 2 MPa. Then place the hot-pressed film in a vacuum drying oven at 250°C for annealing for 3 h, and take it out after naturally cooling to room temperature to obtain a pure PMIA film.

[0068] Comparative Examples 2-5

[0069] Composite films were prepared using the same steps as in Example 1, replacing TS-1 with BNNS, Al2O3, SiO2, and TiO2 respectively (Comparative Examples 2-5).

[0070] Example 1: Microstructure characterization of composite thin films

[0071] The thin film sample prepared in Example 1 was observed by scanning electron microscopy (SEM), and the results are as follows: Figure 1 As shown. By Figure 1 As shown in section A, the composite film has a smooth and dense surface, exhibiting excellent flexibility and the ability to be bent arbitrarily without breaking, indicating that the introduction of TS-1 did not adversely affect the flexibility of the PMIA film. This composite film can undergo subsequent processing operations such as cutting and folding, demonstrating good processability. Figure 1 As shown in sections B and C, the composite film surface is smooth and dense, with TS-1 particles uniformly embedded in the PMIA matrix without obvious agglomeration. The interface is tightly bonded, with no visible voids or cracks. The cross-sectional thickness is uniform (approximately 12 μm), and TS-1 particles are also uniformly dispersed within the film. The film as a whole is dense and non-porous. This uniform and dense microstructure lays the structural foundation for effective interfacial interactions and excellent electrical properties.

[0072] Example 2: Mechanism verification of the interfacial hydrogen bond physical crosslinking network of TS-1 / PMIA composite film.

[0073] To confirm the interfacial interaction mechanism between TS-1 and PMIA, a series of characterization methods, including XRD, FTIR, DSC, and DMA, were performed on Example 1 (0.3 wt% composite film) and Comparative Example 1 (pure PMIA film). The results are as follows: Figure 2 As shown.

[0074] XRD results are as follows Figure 2 As shown in Figure A, the diffraction peak center of the pure PMIA film is located at 2θ≈23.7°, while the diffraction peak center of the 0.3 wt% composite film shifts to 2θ≈25.3°, a shift of approximately 1.6° towards higher angles. According to Bragg's equation (nλ = 2d·sinθ), an increase in diffraction angle implies a decrease in average interchain spacing. Calculations show that the average interchain spacing of the pure PMIA film is 3.75 Å, while that of the composite film decreases to 3.51 Å, a reduction of approximately 6.4%. This indicates that the introduction of TS-1 induces close packing of PMIA molecular chains through interfacial interactions.

[0075] FTIR results as follows Figure 2 As shown in Figure B, the infrared spectrum of the 0.3 wt% composite film is highly similar to that of the pure PMIA film, with a wavelength of 3310 cm⁻¹. -1 (NH stretching vibration), 1650 cm -1(C=O stretching vibration, amide I band), 1535 cm -1 (NH bending vibration, amide II band) and 1240 cm -1 No significant displacement (offset < 2 cm) was observed in any of the characteristic peak positions, including (CN stretching vibration). -1 No new absorption peaks were observed. This clearly indicates that the interaction between TS-1 and PMIA is a physical cross-linking (hydrogen bonding) rather than a chemical reaction that generates new chemical bonds. Therefore, it does not destroy the intrinsic molecular structure of PMIA and avoids the adverse effects of side reactions.

[0076] The DSC results are as follows: Figure 2 As shown in Figure C, the glass transition temperature (T) of a pure PMIA thin film is... g The T value of the composite film at 275.9°C and 0.3 wt% was... g The temperature was increased to 278.5°C, an increase of 2.6°C. g The improvement stems from the fact that the physical cross-linking network introduced by TS-1 effectively restricts the thermal motion of PMIA chain segments, causing the molecular chains to change from a "free state" to a "constrained state." Higher energy is required to excite the chain segment motion, which is crucial for high-temperature applications.

[0077] DMA results are as follows Figure 2 As shown in Figure D, at 150°C, the storage modulus (E') of the 0.3 wt% composite film is 3.10 GPa, which is approximately 48.3% higher than that of pure PMIA (2.09 GPa); at 200°C, it still maintains 2.97 GPa, significantly higher than the 1.84 GPa of pure PMIA. The higher storage modulus indicates that the composite film has a stronger ability to resist electromechanical coupling failure at high temperatures, which helps to maintain structural stability under high electric fields and suppress electromechanical breakdown.

[0078] Based on the above results and Figure 3 The results showed that the titanium hydroxyl groups on the surface of TS-1 formed strong hydrogen bonds with the amide groups on the PMIA chain, anchoring TS-1 in the PMIA matrix and constructing a stable physical cross-linking network. This network constrained the thermal motion of the chain segments at the molecular scale and improved the high-temperature mechanical properties at the macroscopic level, laying a solid foundation for subsequent enhancement of electrical properties.

[0079] Example 3: Analysis of High-Temperature Electrical and Energy Storage Performance of TS-1 / PMIA Composite Thin Film

[0080] To investigate the influence and mechanism of TS-1 on the high-temperature electrical properties of PMIA, systematic tests were conducted on the dielectric frequency domain spectrum, breakdown strength, leakage current density, and energy storage performance of the composite film of this invention. The underlying mechanism was elucidated through band structure analysis, and the results are as follows: Figure 4-8As shown.

[0081] Dielectric frequency domain spectrum results are as follows Figure 4 The results show that, at 150°C and 100 Hz, the dielectric constant of the pure PMIA film is 4.78, while that of the 0.3 wt% composite film is increased to 5.60, representing a relative improvement of 16.9%. Meanwhile, the dielectric loss of all films at 100 Hz is below 0.008, indicating that TS-1 did not introduce additional loss mechanisms while increasing the dielectric constant; instead, it effectively reduced dielectric loss by restricting molecular chain segment movement.

[0082] The film samples prepared in Examples 1-4 (TS-1 addition amounts of 0.3 wt%, 0.1 wt%, 0.2 wt%, and 0.4 wt%, respectively) and Comparative Example 1 (pure PMIA film) were subjected to breakdown strength tests at 150°C. The tests employed a DC boost method (boost rate 200 V / s). 3 mm diameter gold electrodes were sputtered onto both sides of the film, which was then sandwiched between needle-plate electrodes and immersed in silicone oil. Ten sets of effective breakdown voltage values ​​were recorded and divided by the thickness at the test point to obtain the breakdown field strength. The breakdown field strength was then analyzed using a two-parameter Weibull distribution fitting analysis (…). Figure 5 The results are shown in Table 1. Table 1 shows that the characteristic breakdown strength E of the pure PMIA film (Comparative Example 1) is... b The breakdown strength was 459 kV / mm, with a shape parameter β of 9.7. A relatively small β value indicates strong dispersion in the breakdown data and poor film reliability. With increasing TS-1 content, the breakdown strength showed a trend of first increasing and then decreasing: it increased to 566.5 kV / mm at 0.1 wt%, further increased to 609.4 kV / mm at 0.2 wt%, and reached its optimal value of 640.8 kV / mm at 0.3 wt%, representing a 39.5% improvement over pure PMIA. The shape parameter β also increased to 18.5, indicating a significant reduction in breakdown data dispersion and better electrical reliability. When the TS-1 content continued to increase to 0.4 wt%, the breakdown strength decreased to 588.7 kV / mm, attributed to the local agglomeration of excess filler in the matrix, forming electric field concentration points and structural defects, leading to deterioration in breakdown performance. These results indicate that the optimal TS-1 addition amount is 0.3 wt%, at which the composite film possesses both the highest breakdown strength and the best electrical reliability.

[0083] Table 1. Statistical analysis of the breakdown strength of the composite film of the present invention at 150°C.

[0084]

[0085] The leakage current density of the thin film samples prepared in Examples 1-4 and Comparative Example 1 was tested at 150°C and 400 kV / mm. The results are shown in Table 2 and... Figure 6 As shown.

[0086] Table 2. Leakage current density statistics of the composite film of the present invention at 150°C.

[0087]

[0088] From Table 2 and Figure 6 The results show that under harsh conditions of 150°C and 400 kV / mm, the leakage current density of the pure PMIA film (Comparative Example 1) is 3.61 × 10⁻⁶. -5 A / cm 2 As the TS-1 content increases, the leakage current density first decreases and then increases. The leakage current density of the 0.3 wt% composite film is only 1.13 × 10⁻⁶. -6 A / cm 2 Compared to pure PMIA, it reduces leakage current by about an order of magnitude (a reduction of about 96.9%), fully demonstrating the excellent effect of TS-1 in suppressing high-temperature leakage current.

[0089] To reveal the physical reasons for the aforementioned performance improvement, the band structures of PMIA and TS-1 were tested using a spectrophotometer (UV-vis) and an ultraviolet photoelectron spectrometer (UPS). Figure 7 The results show that the highest occupied molecular orbital (LUMO) of PMIA is -2.58 eV, while the conduction band (CB) of TS-1 is -0.05 eV, resulting in an energy level difference of up to 2.53 eV between the two. When the two materials come into contact, the energy level mismatch forms an interfacial barrier. This interfacial barrier plays a dual role: on the one hand, it blocks the injection of electrons from PMIA to TS-1, reducing the probability of charge carriers crossing the interface; on the other hand, the blocked electrons are more easily trapped by interfacial traps, forming localized space charges, which further shield the electric field and suppress subsequent charge carrier injection, thereby synergistically achieving a significant reduction in leakage current and a substantial increase in breakdown strength.

[0090] The energy storage performance of the thin film samples prepared in this invention was tested at 150°C. The hysteresis loop (DE loop) was measured at a frequency of 100Hz using a ferroelectric analyzer, and the discharge energy density (U) was calculated by integration. e The results for the charge / discharge efficiency (η) are shown in Table 3. Figure 8 As shown.

[0091] Table 3. Energy storage performance statistics of the composite film of the present invention at 150°C

[0092]

[0093] From Table 3 and Figure 8 It can be seen that the 0.3 wt% composite thin film exhibits the best energy storage performance: under the condition of efficiency >90%, its discharge energy density (Ua) is the highest. 90 ) up to 9.97 J / cm3 The corresponding electric field is approximately 550 kV / mm, which is for a pure PMIA thin film (3.31 J / cm). 3 The maximum energy storage density (U0) is three times that of approximately 350 kV / mm (an increase of 201.2%); as the electric field continues to increase to near breakdown, the maximum energy storage density (U0) increases. max ) reached 12.09 J / cm 3 The corresponding efficiency is approximately 88%, compared to pure PMIA (5.63 J / cm³). 3 The 114.74% increase indicates that the composite film achieves a good balance between high energy density and high charge / discharge efficiency. Compared with the same amount of BNNS, Al2O3, SiO2, and TiO2, the 0.3 wt% composite film shows a higher U... 90 The improvements were 170%, 164%, 94%, and 149% respectively, demonstrating a significant advantage. This performance leap stems from the dual synergistic gains brought about by the incorporation of TS-1: on the one hand, the high intrinsic dielectric constant and interfacial polarization effect of TS-1 increased the dielectric constant by 16.9% (4.78→5.60); on the other hand, the strong hydrogen bonding crosslinking between the titanium hydroxyl and amide groups and the high interfacial energy barrier formed by the 2.53 eV band mismatch synergistically suppressed high-temperature leakage current, resulting in a 39.5% increase in breakdown strength (459.2→640.8 kV / mm). According to the energy storage density formula U... e =½ε0ε r E b 2 The simultaneous increase in dielectric constant and breakdown strength produces a multiplier effect, resulting in a significant increase in energy storage density far exceeding the linear summation of a single factor. Other fillers, lacking specific functional groups and effective bandgap matching, struggle to achieve the same synergistic effect.

[0094] In summary, this invention is the first to introduce titanium silicate molecular sieve (TS-1) into a PMIA matrix. It utilizes the strong hydrogen bonds between surface titanium hydroxyl groups and amide groups to construct a physical cross-linking network, and leverages a 2.53 eV band mismatch to form a high interfacial energy barrier, achieving a dual synergistic effect of "hydrogen bond cross-linking – energy barrier blocking." This effectively suppresses leakage current under high temperature and high electric field conditions, significantly improving breakdown strength and charge / discharge efficiency. This method requires no surface grafting or coupling agent pretreatment, is simple in process, low in cost, and highly compatible with existing thin-film production lines, showing broad application prospects in the field of high-temperature thin-film capacitors.

Claims

1. A method for preparing a titanium-silicon molecular sieve / meta-aramid composite thin film dielectric material, characterized in that, Includes the following steps: (1) The cleaned and dried PMIA short chopped fibers were added to a polar solvent containing anhydrous LiCl and stirred under heating conditions until completely dissolved to obtain a PMIA dispersion. (2) Add titanium silicate molecular sieve TS-1 powder to the PMIA dispersion, and continue stirring to make TS-1 uniformly dispersed to obtain a composite solution; (3) The composite solution is coated onto a substrate and dried to allow the solvent to evaporate, thereby obtaining a composite film; (4) The composite film is immersed in deionized water to remove residual solvent and impurity ions; (5) Finally, the composite film after soaking is subjected to hot pressing and annealing to obtain the composite film dielectric material.

2. The preparation method according to claim 1, characterized in that, The polar solvent is N,N-dimethylacetamide or N-methylpyrrolidone; the mass ratio of PMIA chopped fibers, polar solvent and anhydrous LiCl is (8-12):(85-90):(1-3).

3. The preparation method according to claim 1, characterized in that, The preparation conditions for the PMIA dispersion are: stirring speed 400-800 rpm, stirring temperature 80-120°C, and stirring time 4-8 h.

4. The preparation method according to claim 1, characterized in that, The amount of TS-1 powder added is 0.1~5 wt% of the PMIA solute mass.

5. The preparation method according to claim 4, characterized in that, The amount of TS-1 powder added is 0.3 wt% of the PMIA solute mass.

6. The preparation method according to claim 1, characterized in that, The preparation conditions for the composite solution are: stirring speed 400-800 rpm, stirring temperature 80-120℃, and stirring time 4-8 h.

7. The preparation method according to claim 1, characterized in that, The coating is applied using a doctor blade, with a blade height of 180-220 μm and a coating speed of 10-30 mm / s; the drying temperature is 80-120℃ and the drying time is 10-12 h.

8. The preparation method according to claim 1, characterized in that, The temperature for soaking in deionized water is 70-80℃, the soaking time is 4-8 days, and the water is changed 2-3 times a day; the conditions for hot pressing are: temperature 200±10℃, pressure 0-5 MPa, time 30-60 s; the conditions for annealing are: temperature 250±10℃, time 3-6 h.

9. A titanium-silicon molecular sieve / meta-aramid composite thin film dielectric material prepared by the preparation method according to any one of claims 1-8.

10. The application of the titanium-silicon molecular sieve / meta-aramid composite thin film dielectric material according to claim 9 in the preparation of high-temperature thin film capacitors.

Citation Information

Patent Citations

  • Titanium silicalite molecular sieve with high energy storage density, polypropylene composite material film and preparation method

    CN118725367A